Fracionamento de mercúrio em amostras de tecido muscular de peixes coletados na área de influência do AHE Jirau - Bacia do rio Madeira utilizando estratégias metaloproteômicas - Moraes, Paula Martin de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Inserted in the context of mercury contamination of Amazonian rivers, this work pursues through metaloproteomic study the identification and characterization of proteins from muscle tissue of three different species of fish from Madeira River that may act as potential biomarkers of toxicity of this element in the region of influence of Jirau Power Plant. The strategies for this study were separated into three distinct components: selectivity, sensitivity and structural. Throughout this research, different methodologies were used in these steps for metaloproteomic study: component of selectivity - 2D PAGE in two-dimensional proteins fractionation; components of sensitivity - SR XRF and GFAAS for mercury identification and quantification in protein spots, respectively; structural component - ESI MS MS in the characterization of proteins identified with mercury in its structure. The species studied were: dourada (Brachyplatystoma rousseauxii), pacu (Mylossoma sp., Myleus sp.) and jaraqui (Semaprochilodus sp.). Among the results, the 2D PAGE proved efficient in protein fractionation of fish muscle tissue. Using qualitative analysis by SR XRF was possible to identify the presence of mercury in the spot 68 of dourada (molar mass of 20.8 kDa and pI 5.6) and spot 72 of pacu (molar mass of 19.8 kDa and pI 7.5). Determinations by GFAAS allowed the mercury quantification in muscle tissue and in 28 spots that showed concentrations from 11.3 to 41.2 mg g-1 of mercury in its composition; these results enabled an estimative calculation of the number of mercury atoms per protein molecule between the spots studied. After analysis by ESI MS MS it was possible to characterize eight proteins with different isoforms in 21 spots that showed pI 3.5 to 9.8 and molar mass between 9.9 and 18.1 kDa, indicating that these proteins may be potential candidates for mercury biomarkers in ...

Inserido na realidade de contaminação dos rios amazônicos pelo mercúrio, este trabalho busca, por meio do estudo metaloproteômico, a identificação e a caracterização de proteínas do tecido muscular de três espécies diferentes de peixes do rio Madeira que possam atuar como possíveis biomarcadores da toxicidade deste elemento na região de influência do Aproveitamento Hidrelétrico de Jirau (AHE JIRAU). As estratégias para este estudo foram separadas em três componentes distintos: de seletividade, de sensibilidade e estrutural. Ao longo desta pesquisa, diferentes metodologias foram empregadas nessas etapas para o estudo metaloproteômico: componente de seletividade - 2D PAGE no fracionamento bidimensional das proteínas; componentes de sensibilidade - SR XRF e GFAAS para identificação e quantificação do mercúrio nos spots proteicos, respectivamente; componente estrutural - ESI MS MS na caracterização das proteínas identificadas com mercúrio em sua estrutura. As espécies de peixes estudadas foram: dourada (Brachyplatystoma rousseauxii), pacu (Mylossoma sp., Myleus sp.) e jaraqui (Semaprochilodus sp.). Entre os resultados obtidos, a 2D PAGE se mostrou eficiente no fracionamento proteico do tecido muscular de peixes. Utilizando análises qualitativas por SR XRF foi possível identificar a presença de mercúrio no spot 68 da dourada (massa molar 20,8 kDa e pI 5,6) e no spot 72 do pacu (massa molar 19,8 kDa e pI 7,5). Determinações por GFAAS permitiram a quantificação do mercúrio no tecido muscular e em 28 spots, que apresentaram concentrações de 11,3 a 41,2 mg g-1 de mercúrio em sua composição; esses resultados possibilitaram o cálculo da estimativa do número de átomos de mercúrio por molécula de proteína entre os spots estudados. Após análise por ESI MS MS, foi possível caracterizar oito proteínas com diferentes isoformas em 21 spots que apresentaram pI de 3,5 a 9,8 e massa molar ...
Mercury fractionation in muscle tissue from fishes collected in the area of influence of Jirau Power Plant-Basin Madeira river using metaloprotemics strategies
Keywords: Peixe - Efeito da poluição da agua; Eletroforese bidimensional; Metaloproteinas; Indicadores (Biologia); Madeira, Rio (RO e AM); Fishes - Effect of water pollution on